Psychology of ultrarunning: evaluating validation, social identity, and disharmony in the long-distance experience - Mueller, T. S. (Journal of Clinical Sport Psychology, 2025)
This study (N = 394) investigated motivators and detractors in ultrarunners. Latent factors Validation, Social Identity, and Disharmony were identified. Network analysis supported Social Identity through the hub node "ultra tells a lot about me" associated with "glimpse of who I am" with "can tell a lot about the person." The regression "upset if unable to participate," F(5, 365) = 16.90, p < .001, R2 = .019, view Cognitive Involvement (t = 4.54, p < .001), Disharmony (t = 2.96, p = .003), and Social Identity (t = 2.41, p = .016) as significant predictors. "Lone Wolf" isolationist runners were highly masculine and motivated by emotional involvement. Back and middle of the pack runners viewed Disharmony differently than front of the pack runners. Text analysis sentiment "Affect Friends and Family" supports the Disharmony factor. Event promoters and product marketers should acknowledge ultrarunning motivators and detractors, and promote wellness among competitors.